Modelling Of Tool Life When Milling Nickel Base Alloys With Two Different Coated Carbide Insert. - K., Kadirgama (2008)
This paper discusses the development of the first-order model for predicting the tool life in end-milling operation of Hastelloy C-22HS nickel base superalloy when employing two differently coated carbide cutting tools. The first-order equations of tool life are developed using response surface methodology (RSM). The cutting variables used in this study are the cutting speed, feed rate, and axial depth of cut. The analysis of the obtained models is supported using a statistical software package. From this study, it is found that the models are able to predict values of tool life close to those readings recorded experimentally with a 95%-confidence interval. The tool life first order equations show that feed rate is the most dominant factor, followed by axial depth of cut, and then cutting speed. In addition, the study indicates that inserts coated with a single TiAlN layer outperform the other type of inserts,which are with multiple-layered coating.